Topics in Modal Analysis I, Volume 5 Proceedings of the 30th IMAC, A Conference on Structural Dynamics, 2012 - Allemang, R.; De Clerck, J.; Niezrecki, C.; Blough, J.R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Topics in Modal Analysis I, Volume 5. Proceedings of the 30th IMAC, A Conference and Exposition on Structural Dynamics, 2012, the fifth volume of six from the Conference, brings together 53 contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Modal Parameter Identification Damping of Materials and Members New Methods Structural Health Monitoring Processing Modal Data Operational Modal Analysis Damping Excitation Methods Active Control Damage Detection for Civil Structures System Identification:  Applications.
Compressed Sensing Applied to Modeshapes Reconstruction -- Automated Modal Analysis Based on Frequency Response Function Estimates -- Operational Modal Analysis Using a Fast Stochastic Subspace Identification Method -- Tutorial Guideline VDI 3830: Damping of Materials and Members Model Calibration and Validation for Material Damping using Finite Element Analyses -- Damping Properties Assessment of Very Highly Compliant Sandwich Materials: Are Traditional Methods Really Too Old? -- Wind-induced Vibrations in the European Court Towers -- Time-frequency Domain Modal Parameter Estimation of Time-varying Structures Using a Two-step Least Square Estimator -- Comparison of Modal Parameters Estimated From Operational and Experimental Modal Analysis Approaches -- Implementation of an SDOF Parameter Estimation Method With Generalized Residuals -- Autonomous Identification of the Fast Time-varied Modal Parameters -- An Efficient Iterative Algorithm for Accurately Calculating Impulse Response Functions -- A “Local Solve” Method for Extracting Modal Parameters from Inconsistent Data -- An Overview of the Transmissibility Concept and its Application to Structural Damage Detection -- From Discretization to Continuous; Advanced Mechanical Measurements Using Continuous Scanning Methods -- Measurement of Friction Contact Parameters for Nonlinear Dynamic Analysis -- Advanced Frequency-domain Modal Analysis for Dealing With Measurement Noise and Parameter Uncertainty -- Updated Cepstral Methods for Operational Modal Analysis -- A Non-hermitian Joint Diagonalization based Blind Source Separation algorithm for Operational Modal Analysis -- Symbolic Dynamics-based Structural Health Monitoring -- Estimating The Elastic Period of Masonry Towers -- Operational Analysis in the Launch Environment -- Non-contact Operational Modal Analysis of an Optical Membrane for Space Application -- Padding Dynamic Stiffness Using Impedance Modeling of Helmet-head System -- Dynamic Stiffness-based Test Systems For Viscoelastic Material Characterization: Design Considerations -- Fixed Base FRF Using Boundary Measurements as References - Analytical Derivation -- Fixed Base FRF Using Boundary Measurements as References - Experimental Results -- A Comparison of Multiple Impact Testing Methods -- Advances in Six Degree of Freedom Vibration Tests -- Converting a Slip Table Random Vibration Test to a Fixed Base Modal Analysis -- Refinements on Estimating Fixed Base Modes on a Slip Table -- A Frictionless Lightweight Active Vibration Control Mount for Small UAS -- Embedded Active Vibration Cancellation of a Piston-driven Cryocooler for Nuclear Spectroscopy Applications -- Advanced Response Limiting Technique for Lightly Damped Structures -- Active Control of Beam Vibration Using Non-model Based Algorithm -- Damage Identification Using Experimental Modal Analysis and Adaptive Neuro- Fuzzy Interface System (ANFIS) -- Process Noise Identification and Observer Design for the Large Binocular Telescope -- Modal Analysis of a Heliostat for Concentrating Solar Power -- Extension of Subspace Identification to LPTV Systems: Application to Helicopters -- Dynamic Characterization of Structural Joints Using FRF Decoupling -- Identification of Hysteretic Systems Using NARX Models, Part I:  Evolutionary Identification -- Kalman Filtering With Model Uncertainties -- Ground Vibration Testing of the Predator B UAS with MTS Chin-Mount Structure -- Acoustic Fluid-structure Interaction of Cars and Ships (Tutorial) -- System Identification in Rotating Structures Using Vibration in Modal Analysis -- Some Considerations of Boundary Conditions in Dynamic Testing -- Boundary Constrained Modal Test Method for Large Scale Highly Flexible Structures -- A Comparison of Non-parametric Techniques for FRF Estimation Using Pure Random Excitation -- Exciter Impedance and Cross-Axis Sensor Sensitivity Issues in FRF Estimation -- Modal Testing and FE Model Updating of a Lively Staircase Structure -- Tracking the Evolution of Modal Properties of a Solid Propellant Launcher During Static Firing Test.
Keywords: Vibration; Dynamical systems; Dynamics; Aerospace engineering; Astronautics; Mechanics; Mechanics, Applied; Vibration, Dynamical Systems, Control; Aerospace Technology and Astronautics; Solid Mechanics